Management of Antipsychotic Therapy in Patients with Schizophrenia - Handayany, Gemy Nastity; Mulat, Trimaya Cahya (International Journal of Statistics in Medical Research, 2025)
Antipsychotic therapy is the main approach in the treatment of schizophrenia, but there is often irrational use due to inappropriate drug selection, inappropriate dosage, and long-term use without evaluation. Factors that support therapeutic rationality include adherence to clinical guidelines, selection of safer antipsychotics, and optimal management of side effects. Therefore, it is important to evaluate the factors that contribute to rational and irrational therapy in the use of antipsychotics in patients with schizophrenia. This study aims at antipsychotic medication management and factors that cause irrational therapy, as well as evaluating factors that support therapeutic rationality in the use of antipsychotics in schizophrenic patients. This study used a cross-sectional study design involving schizophrenia patients undergoing antipsychotic therapy in a psychiatric hospital. Data were collected through patient medical records and interviews with health workers. Quantitative data were analyzed using descriptive statistics and inferential tests, including chi-square and regression analysis, to determine the association between patient characteristics and antipsychotic selection as well as therapy rationality. The results showed that 26.7% of patients received irrational therapy, with the main causes being inappropriate drug selection (45%), inappropriate dosage (30%), and long-term use without evaluation (25%). Meanwhile, 73.3% of patients received rational therapy, with the main contributing factors being adherence to clinical guidelines (50%), selection of safer antipsychotics (30%), and good side effect management (20%). Irrational antipsychotic therapy remains a significant problem in the management of schizophrenia. Adherence to clinical guidelines and appropriate therapy selection can improve treatment effectiveness and reduce the risk of side effects. Regular evaluation and a multidisciplinary approach are needed to improve the rationality of antipsychotic therapy.